Programa educativo de actividades lúdicas en la lectoescritura de los estudiantes en la Institución Educativa N°6010130 Santa Amelia, Pevas 2023 - Murrieta López, María Margarita (2024)
The central purpose of the study was to evaluate the educational program of recreational activities in improving literacy in I.E. students. N° 6010130 Santa Amelia district of Pevas 2023. The study was an applied quantitative approach with a quasi-experimental design that applied a pre-test and post-test. As an instrument, a 10-question questionnaire was used. The sample was made up of 19 students from the experimental group and 12 from the control group. The study's results determined that students in the experimental group to whom the educational program was applied obtained a higher average (12.58) than the students in the control group (9.58) in literacy and its dimensions. He concluded that the difference in averages between the students of the experimental group, subjected to the educational program in question, and those of the control group, who followed the traditional method, was statistically significant (p-value < 0.05), indicating that the former had notably higher performance in literacy and instructed skills.